2015
DOI: 10.1055/s-0034-1543948
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight, Insulin Resistance, and Blood Pressure in Late Preterm Infants

Abstract: As compared with AGA, SGA late preterm infants had lower diastolic blood pressure and lower IGF-1 during the 2nd week of life, but similar insulin resistance and lipid profile. We speculate that although metabolic derangements in SGA infants could have occurred at a much earlier age in fetal life, their manifestations may not be present in the immediate postnatal life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
3
0
1
Order By: Relevance
“…While SGA subjects had lower insulin secretion and resistance at birth, 2 we observed no significant differences in HOMA indices in infancy at age 2 years comparing SGA and OGA infants. This observation is consistent with a previous report in 40 SGA and 41 appropriate‐for‐gestational‐age (AGA) infants at age 2 weeks 4 and another study of 85 SGA and 23 AGA infants at age 1 year 5 . Taken together, insulin secretion and resistance appear to be normalised in SGA subjects by age 1–2 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While SGA subjects had lower insulin secretion and resistance at birth, 2 we observed no significant differences in HOMA indices in infancy at age 2 years comparing SGA and OGA infants. This observation is consistent with a previous report in 40 SGA and 41 appropriate‐for‐gestational‐age (AGA) infants at age 2 weeks 4 and another study of 85 SGA and 23 AGA infants at age 1 year 5 . Taken together, insulin secretion and resistance appear to be normalised in SGA subjects by age 1–2 years.…”
Section: Discussionsupporting
confidence: 92%
“…SGA infants have low insulin secretion and resistance at birth, 2 but may become more insulin resistant in childhood, 3 while research data in infancy have been inconsistent. Two studies reported no alterations in insulin resistance in SGA infants at age 2 weeks 4 or 1 year, 5 while two other studies reported lower insulin resistance in SGA infants relative to normal birth weight infants at age 1–2 years 6,7 . SGA infants at birth have lower concentrations of leptin and adiponectin 8,9 which are important adipokines in regulating insulin sensitivity 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Aly et al [7] did not detect any evidence of insulin resistance in 81 late preterm infants (i.e., 41 AGA and 40 SGA) who underwent assessment of plasma insulin levels on the first day of life and in the second week of life. Accordingly, Bagnoli et al [22] investigated glucose homeostasis in 18 late preterm and 18 term infants at birth and did not report any difference in insulin concentration or the HOMA-IR index among groups.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance represents an early marker of the subsequent development of type 2 diabetes. However, the timing and origin of insulin resistance have not been clarified yet [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…В целом ряде исследований определена связь «догоняющего роста» маловесных детей с риском развития метаболического синдрома в младшем и старшем школьном возрасте [36][37][38][39]. Причем отмечено, что такие нарушения, как инсулинорезистентность, склонность к высокому систолическому артериальному давлению (АД), более высокий процент жира в организме, нарушение гликемического профиля, определяются в возрасте 25-28 лет у лиц с ОНМТ и ЭНМТ при рождении [36].…”
Section: функциональные особенности половой системы связанные с морфunclassified